Ideology and international relations. (August 2020) - Gries, Peter; Yam, Paton Pak Chun
Abstract : What is the relationship between ideology and international relations (IR)? The extant literature focuses on how the former shapes the latter. Confrontation between Liberalism and Fascism, Communism, and Authoritarianism have sequentially structured IR over the past Century. While such all-encompassing Ideologies may unify the people of different nations in (often opposing) worldviews, liberal/left and conservative/right ideologies can divide citizens within nations. Dimensions of ideology like social dominance orientation (SDO) and right-wing authoritarianism (RWA) also shape international attitudes in distinct ways. These individual-level ideologies and their attendant worldviews shape state-level foreign policies and system-level IR (the micro–macro link) through elite decision-making and public opinion. An emerging literature also reverses the causal arrow, exploring how health, terrorism and other system-level threats can shape individual-level ideologies. This review essay should reveal the centrality of political psychology to IR: how ideologies powerfully shape the very worlds that we experience and act upon—and their vital role in driving war and peace.